Elastin Expression and Elastic Fiber Thickness in The Uterosacral Ligament of Women With Uterine Prolapse - Supriadi, Erwin (Indonesian Journal of Obstetrics and Gynecology, 2011)
Objective: To measure and correlate bet-ween elastin expression and elastic fibre thickness in the uterosacral ligaments of women with uterine prolapse. Method: This analytic with cross sectional study was done in January - March 2011. Specimens were obtained from the parafin block of uterosacral ligaments of women having uterine prolapse (prolapse group, n = 16) and the same location in patients with no prolapse having simple hysterectomy, radical hysterectomy or staging laparotomy (control group, n = 16) who came to Dr. Hasan Sadikin hospital and its network. The percentage of elastin positive tissue and elastic fibre thickness were measured by immunohistochemistry from random field readings per sample. The examiner was unaware of sample identity and the patientsâ clinical history. Result: The risk factors (age, parity and vaginal delivery) were compared between the control and prolapse groups, and there were no difference of body mass index between the groups. Immunohistochemical staining and morphometric analysis indicated there were significant different beween elastin expression in the prolapse group compare with the control group (p < 0.001). The mean thickness of elastic fibres was 0.938 Î¼m in the group with uterine prolapse and 2.244 Î¼m in the control groups (p = 0.02). Elastin expression was associated with elastic fiber thickness (r = 0.589 and p = 0.016). Conclusion: In this cross-sectional study investigating elastin changes in women with prolapse, there was correlation between elastin expression and elastic fiber thickness in uterosacral ligament of women with uterine prolapse. [Indones J Obstet Gynecol 2011; 35-2: 79-83] Keywords: elastin, uterosacral ligament, uterine prolapse